Measuring professional preparedness of would-be teachers for pedagogical activity based on criteria-level estimation - M. A. Golovchin (Russian Journal of Economics and Law)
Objective: to determine the level of future teachers’ professional readiness for pedagogical activity using the statistical method of analysis based on the secondary data of a sociological research; to assess the factors affecting the above level.Methods: the study applied an index method of generalizing the data of sociological measurements to calculate the index of professional readiness for pedagogical activity (Iprpa). As part of the assessment, we used the data of the sociological survey conducted by VolNTs RAS in May-June 2023 among graduate students majoring in pedagogy at vocational schools and universities of Vologda oblast.Results: based on generalization of the study of professional readiness for pedagogical activity (futher – PRPA), a theoretical model of criterion-level assessment of this phenomenon was proposed. Within the model approbation, the readiness of future teachers for professional activity was assessed. Calculations showed that 24.6 % of the surveyed graduates had a high level, 44.6 % had an average level, and 30.8 % had a low level of PRPA. At the same time, university graduates had a lower level of readiness for school work than those who get a profession in colleges. The correlation analysis revealed that future teachers’ PRPA is strongly influenced by the presence of professional vocation as a sense of spiritual connection with the profession, and is influenced weakly by the purchasing power of their income. The spread of negative perceptions of the teaching profession among graduates usually reduces their readiness to work in the profession.Practical significance: the study proposes a step-by-step algorithm for assessing professional readiness for pedagogical activity using a sociological database. It is suggested that the process of the PRPA formation is influenced not only by the educational organization, but also by the future specialist personality. In particular, it concerns the inner desire to see oneself in pedagogical activity as an established professional, which is not always formed in the process of training at vocational schools and universities (especially if admission to the major was associated with “negative selection”). In this regard, we formulate proposals to overcome the effect of “negative selection” in the professional training of future teachers.Scientific novelty: the study clarifies the approach to the category of “professional readiness for pedagogical activity” and proposes a methodology for assessing the PRPA level, which includes a theoretical model of criterion-level assessment of this phenomenon, as well as an algorithm for calculating the final index of PRPA.